Sustitución parcial de la Harina de Trigo por Harina de Nopal (opuntia ficus-indica) en la elaboración de pan. - Cando Chasiloa, Karolina Elizabeth (2020)
This analysis aimed to develop a research study on the partial substitution of wheat flour with prickle pear flour (Opuntia ficus-indica) in bread making. Methodologies, physicochemical and nutritional analyses were considered regarding the flour, bread processing, and its possible cost of production. In order for the production of prickle pear bread (Opuntia ficus-indica), it was considered that the use of cladodes in a state of maturity from one to three years were what best provides its nutrients, followed by a dehydration process, which is placed in 2cm-thick strips dehydrator at a temperature of 65-70ºC from three to four hours in order to obtain the prickle pear flour. In addition, it was established that to guarantee safety, physico-chemical and nutritional analyses must be carried out. Therefore, a practice guide was proposed to conduct these analyses. It was considered that for making bread, the best formulations are 90% wheat flour with 10% prickle pear flour up to a maximum of 80% wheat flour and 20% prickle pear flour, since the prickle pear flour content helps to enrich the wheat flour. It provides a lot of fiber, calcium, and vitamins. In addition, thorough formulas, the cost of production for tin loaf bread with a presentation of 475g was analyzed, noting that the product is innovative and it helps in feeding people due to its nutritional content.